Electric Stimulation Pada Luka Kaki Diabetik: Literature Review: Electrical Stimulation in Diabetic Foot Ulceration: a Literature Review - Lestari, Imtinan Karina; Sugiyarto; Sumardino (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2022)
Diabetic foot ulcers occur in diabetic feet due to impaired blood circulation in the legs, nervous system disorders, and infection due to decreased body immunity. One of the new interventions that can be performed on diabetic feet is electric stimulation. Electric Stimulating aims to re-establish cell migration by mimicking a physiological current of injury (COI), which is an electric current from the center of the body to the injured nerve or muscle, or to other tissues that are stimulated. The purpose of this literature review was to analyze the application of electric stimulation for diabetic foot ulceration based on empirical studies over the last five years. The design of this research was a literature review. The method used was to search for articles with keywords that have been determined in an electronic database related to electric stimulation in diabetic foot wounds. The electronic database comes from Google Scholar, Researchgate, Wiley, EBSCO and Pubmed in the last five years as many as 8 journals that match the inclusion criteria set by the authors. The results of the analysis showed that electric stimulation on diabetic foot wounds could help wound healing and smooth peripheral tissue perfusion. This literature review can be a reference in performing nursing care and applied in the treatment of diabetic foot wounds in nursing services.